1999
DOI: 10.1093/toxsci/50.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls (PCBs) selectively disrupt serotonergic cell growth in the developing Spisula embryo

Abstract: Polychlorinated biphenyls (PCBs) are ubiquitous environmental contaminants that exert neurotoxic effects during embryonic development. The present study demonstrates that early embryonic exposure to a mixture of PCBs (Aroclor 1254) results in a decrease in serotonergic cell growth. Using a novel, marine invertebrate embryo model, Spisula solidissima, immunocytochemistry, and confocal microscopy techniques, a dose-dependent decrease in serotonergic cell number was quantified within 24 h of exposure. This effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…We also plan to determine whether decreased p120 levels and function are restricted to the nervous system. Because we have shown in separate experiments that PCBs target neuronal growth in surf clams (16,17) and that the time course of this reduction is the same for both p120 and the serotonergic system, we hypothesize that the developing nervous system is most sensitive to changes in p120.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We also plan to determine whether decreased p120 levels and function are restricted to the nervous system. Because we have shown in separate experiments that PCBs target neuronal growth in surf clams (16,17) and that the time course of this reduction is the same for both p120 and the serotonergic system, we hypothesize that the developing nervous system is most sensitive to changes in p120.…”
Section: Discussionmentioning
confidence: 94%
“…All animals were maintained and handled in accordance with policies of the Institutional Animal Care and Use Committee at the MBL. Standard surf clam in vitro fertilization and culture methods were used (16). At the swimming blastula stage, embryos were transferred to 4-L aerated tanks at a concentration of 100 mL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCBs have been shown to impair serotonergic and other monoamine neurotransmitter systems in animal models as diverse as mammals, fish and clams (Chu et al 1996; Thomas 1997, 2001;Seegal et al 1985Seegal et al , 1986Seegal et al , 1990Seegal et al , 1991aSmith et al 1999). Several laboratory studies in rats have shown that PCBs at sub-lethal doses influence dopamine (DA), norepinephrine, serotonin (5-hydroxytryptamine, 5-HT), and their metabolite concentrations in discrete brain areas (Chu et al 1996;Seegal et al 1985Seegal et al , 1986Seegal et al , 1991a.…”
Section: Introductionmentioning
confidence: 99%
“…Polychlorinated biphenyls (PCBs) have been shown to impair serotonergic and other monoamine neurotransmitter systems in animal models as diverse as mammals, fish and clams (Khan & Thomas, 1997, 2001Seegal, Brosch, & Bush, 1986;Smith, Barker, Barker, Jessen-Eller, & Reinisch, 1999). Some PCBs reduce serotonin (5-hydroxytryptamine; 5-HT) concentrations in certain brain areas in rats (Seegal et al, 1986) and fish (Khan & Thomas, 1997, 2001.…”
mentioning
confidence: 99%